Gaya Bahasa Perulangan dalam Film Jembatan Pensil Karya Hasto Broto pada Unggahan Akun YouTube Dailykmps - Nur Ainun Husaen; Idawati Idawati; Tuti Wijayanti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to identify various forms of repetitive language styles and analyze the function of their use in the film Jembatan Pensil by Hasto Broto on the upload of the Dailykmps YouTube account. This research uses a stylistic approach, which is a study that analyzes language styles and their functions in the context of speech. The research data was obtained from the dialogues of the characters in the film, then analyzed through the stages of data reduction, data presentation (data display), and conclusion drawn. The results of the study show that there are ten forms of repetitive language styles, namely epizeukis, anaphora, tautotes, and so on. In addition, the function of the repetitive language style in this film is found in ten aspects, including strengthening the expression of feelings, emphasizing meaning, and strengthening the message. Thus, the repetitive language style in the film Pencil Bridge plays an important role in strengthening the meaning, livening up the atmosphere, and conveying the moral values contained in the story. The scientific contribution of this research lies in strengthening the study of stylistics through its application to film media, especially in the analysis of repetitive language styles, so that the findings of this research can be used as a reference for future studies that focus on audiovisual works.